Clinical Assessment and Outcomes of Endoscopic Endonasal Trans-Sphenoidal Surgery for Pituitary Adenomas among Iraqi Patients - Amjed Jawad Kadhum AlJawad; Khalid Z. Ghudhaib AlSary; AlHasan Amjed Jawad AlJawad (Academic Journal of Clinicians, 2025)
Pituitary adenoma (PA) is considered as an emergency endocrine and neurosurgical condition due to its potential for severe and sometimes life-threatening consequences, necessitating immediate care at specialized medical facilities. Although Endoscopic endonasal trans-sphenoidal surgery is currently represent the gold standard approach for pituitary tumors, studies, in Iraq, long-term follow up studies are so scanty and no study available with regard to this topic at our setting in Karbala that clinically this approach and its outcomes among Iraqi patients with pituitary adenomas., therefore, the purpose of this article is to retrospectively evaluate the outcomes of the trans-sphenoidal technique for pituitary tumors in Iraq. Wherefore, a total of 34 Iraqi patients, 14 males and 20 females with a median age of 46 years were enrolled in this study and their data were analyzed. Findings revealed that after Endoscopic endonasal surgery, majority of the patients had improvement in their symptoms and overall outcomes and this approach was safe effective option for treatment of pituitary adenomas among Iraqi patients It has favorable outcomes, low risk of complications, and minimally invasive nature. However, it is essential to highlight that the presence of residual tumors increase the likelihood of recurrence. Therefore, we propose to use radiotherapy after surgery to minimize the risk of recurrence